2006
DOI: 10.1002/humu.20301
|View full text |Cite
|
Sign up to set email alerts
|

DLG5 variants contribute to Crohn disease risk in a Canadian population

Abstract: Variants in the gene encoding the DLG5 scaffolding protein have been reported to be associated with increased risk of inflammatory bowel disease (IBD) and particularly Crohn's disease (Crohn disease; CD). These findings have not been uniformly replicated in follow-up studies. In this study we genotyped a cohort of 402 Canadian CD and 179 ulcerative colitis (UC) patients and 537 healthy controls for three IBD/CD-associated DLG5 variants. Our data reveal that the common DLG5 haplotype (A), which was previously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The association of the R30Q variant with IBD has been supported in some studies [12,24,25,27], but failed to be replicated in others [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of the R30Q variant with IBD has been supported in some studies [12,24,25,27], but failed to be replicated in others [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Stoll et al, [12] identified an IBD risk-associated DLG5 haplotype D that is uniquely distinguished by the 113A variant of R30Q. The association of R30Q with IBD has been replicated in other studies from several different patient populations [24][25][26]. Friedrichs et al, found a male-specific association of the R30Q variant with CD, with no association of the R30Q variant with women, nor with the entire sample of men and women [27].…”
Section: Introductionmentioning
confidence: 94%
“…MAGUK proteins are known to form scaffolds for other proteins involved in intracellular signal transduction and could therefore interfere with the integrity of the epithelial barrier. Since the publication of the index paper, germline variation of DLG5 has been studied in a large number of populations but replication has only been demonstrated in a few (77) (Table 3) (51,57,60,76,(79)(80)(81)(82)(83)(84)(85)(86)(87)(88). Whether true genetic heterogeneity, phenotypic differences between patient populations, and/or stratification of control groups are responsible for these discrepancies remains a subject of intense debate, but a meta-analysis of most published studies suggests it does not have a major role to play in IBD susceptibility (78).…”
Section: Dlg5mentioning
confidence: 99%
“…Present approaches have not been able to discern whether these other genes or the class Ⅱ genes are the true risk genes in the HLA locus. [79][80][81][82] , multiple polymorphisms in the MDR1/ABCB1 gene on chromosome 7q [83][84][85][86][87][88][89][90][91][92] , and polymorphisms in the DLG5 gene on chromosome 10q [70,[93][94][95][96][97][98][99][100][101][102] . (See section C.4.1.)…”
Section: Hla Associationsmentioning
confidence: 99%